Synthesis and Characterization of Certain Biodegradable Random Aliphatic Copolyesters - Ravi, A.; Nanthini, R.; Karunanidhi, M.; Jaisankar, V. (Asian Journal of Chemistry, 2010)
Biodegradable aliphatic random copolyesters poly(butylene succinate-co-butylene adipate) and poly(butylene succinate-co-butylene azelate) were synthesized from 1,4-butane diol, succinic acid and adipic acid/azelaic acid through direct melt polycondensation with titanium tetra isopropoxide as a catalyst. These polyesters were characterized by viscosity measurements, 1H nuclear magnetic resonance spectroscopy, gel permeation chromatography and X-ray diffraction analysis. Thermal properties have been analysed using differential scanning calorimetry. The percentage of biodegradation of the synthesized copolyesters was investigated by enzymatic hydrolysis using the enzyme Candida cylindracea lipase. It appears that the key factor affecting the degradation was its crystallinity. This kind of novel biodegradable polymers are expected to have potential applications as environment friendly materials.